Screening of silver resistance gene in clinical isolates and determination of Minimum Inhibitory Concentration (MIC) for silver nitrate - Safain, Kazi Sarjana (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.